2022
DOI: 10.32942/osf.io/ewq64
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of an obesogenic diet on behaviour and cognition in zebrafish (Danio rerio): traits average, variability, repeatability, and behavioural syndromes

Abstract: The obesity epidemic, largely driven by the accessibility of ultra-processed high-energy foods, is one of the most pressing public health challenges of the 21st century. Consequently, there is increasing concern about the impacts of diet-induced obesity on behaviour and cognition. While research on this matter continues, to date, no study has explicitly investigated the effect of obesogenic diet on variance and covariance (correlation) in behavioural traits. Here, we examined how an obesogenic versus control d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Our study in the F0 parental generation revealed that zebrafish on an obesogenic diet displayed tendencies consistent with poor cognition. That is, some individuals in the obesogenic diet group performed consistently worse in aversive learning tests than control fish, which seemed to have led to higher repeatability estimates (Anwer, O'Dea, et al, 2022 ). Recently, two other studies examined cognitive function in zebrafish following a HFD treatment (Meguro et al, 2019 ; Picolo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study in the F0 parental generation revealed that zebrafish on an obesogenic diet displayed tendencies consistent with poor cognition. That is, some individuals in the obesogenic diet group performed consistently worse in aversive learning tests than control fish, which seemed to have led to higher repeatability estimates (Anwer, O'Dea, et al, 2022 ). Recently, two other studies examined cognitive function in zebrafish following a HFD treatment (Meguro et al, 2019 ; Picolo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, male and female zebrafish from the F0 (parental) obesogenic treatment group (see our paper (Anwer, O'Dea, et al, 2022) for more details on the F0 cohort) were significantly heavier than their control counterparts after 22 weeks of diet exposure (treatment female -control female est = 0.13, df = 171, t = 9.28, p < .0001; treatment male -control male est = 0.06, df = 171, t = 4.32, p = .0002).…”
Section: Body Weight and Fasting Blood Glucosementioning
confidence: 99%
See 2 more Smart Citations
“…Here, we address the question of how obesogenic diets in the parental generation (F0) can impact offspring cognition intergenerationally (F1) in zebrafish (Danio rerio). We conducted a multifactorial experiment by breeding four F1 groups from F0 fish from our previous work (Anwer, O'Dea, et al, 2022) with and without exposure to an obesogenic diet (i.e., treatment mothers × treatment fathers, or F1T; treatment mothers × control fathers, or F1M; treatment fathers × control mothers, or F1P; control mothers × control fathers, F1C). In our previous study (Anwer, O'Dea, et al, 2022), we examined effects of an obesogenic diet on the immediate generation (F0).…”
Section: Introductionmentioning
confidence: 99%